ARTISTIC WORK AS CREATIVITY AND BEAUTY (Academicia Globe: Inderscience Research, 2022)
The article is relevant, devoted to the analysis and development of art since ancient times. The term "art" is diverse. In a broad sense, it means a high level of skill in any field of activity, indicates the beauty and perfection of its product. The reason for the division of art into types is the variety of types of human social practice in the field of artistic development of the world, based on the aesthetic diversity of reality.